Radiocarbon dating of Early Egyptian pot residues - Dee, M. W.; Wengrow, D.; Shortland, Andrew J.; Stevenson, A.; Brock, Fiona; Bronk Ramsay, Christopher (Peeters Publishers., 2016)
A number of absolute dating techniques are now used in archaeology, from dendrochronology to a variety of luminescence and radiometric methods.1 However, radiocarbon dating remains the most effective approach for the early historic periods. This is largely because of the levels of precision achievable, but also due to the diversity of materials that can be dated, and the ease with which radiocarbon dates can be connected to specific events in the past. Radiocarbon dating can be employed on all carbon-containing materials that are biogenic in origin. Common sample types include items fashioned from plant material, such as textiles and basketry, and the remains of animal and human tissue. Radiocarbon estimates denote the time elapsed since the antecedent organism ceased exchanging carbon with its environment. For human and animal remains this is invariably taken to be the time of death, and for plants it is most commonly the time at which the material was harvested or felled. With the advent of accelerator mass spectrometry (AMS) in the 1980s, it became possible to conduct radiocarbon analysis on samples several orders of magnitude smaller than preceding techniques.2 Typically, AMS can produce reliable dates on as little as 10 mg of plant material and just 250 mg of whole bone powder. As a result, AMS accounts for a large proportion of the dates made on archaeological samples. No form of radiocarbon dating can, however, provide direct estimates for the age of lithic or ceramic artefacts. The principle difficulty lies in relating any datable material obtained to the manufacture or use of the object in question. In fact, carbonaceous inclusions in such materials are likely to be of geological age, and therefore beyond the 50,000 year detection limit of the technique. Consequently, there remains a disjunction between radiocarbon results and dates based on ceramic seriation. One possibility at bridging this divide comes from the radiocarbon dating of organic residues adhered to specific ceramic types. This prospect was investigated for Early Egypt by an interdisciplinary research team from the University of Oxford, University College London and Cranfield University.